Living fully : dare to step into your most vibrant life - Ervin, Mallory (Convergent, 2022)
"An irresistible guide to living without holding back, from the vibrant lifestyle entrepreneur and host of the Living Fully podcast. Mallory Ervin is known for exuding energy, joy, and laughter. But despite her public accomplishments, Mallory is no stranger to battling unhealthy attachments to performance and success. Now, in her unforgettable debut book, Mallory invites readers to see how her surprising journey-from achievement and accolades to devastating, never-before-shared lows-guided her and led her to a deeply fulfilling life. In Living Fully, Mallory shares her personal story of overcoming the unhealthy and damaging patterns in her life and shows readers how to trade this for something completely new and more rewarding. What she discovered was there had always been a different life available to her, one that she had not yet seen. Now she encourages readers to resist a "just fine" existence and to step into a life they never dared to imagine before. Through inspiring stories and practical advice Mallory encourages readers to: stop returning to a "just getting by" mentality shift perspective so blessings don't become burdens remember that life's curveballs don't have to knock you off your feet identify your passions and get back to your truest self slow down and enjoy the extraordinary in the everyday moments quiet the voice of fear get clear on the life you want "I wrote this to be your wake-up call, the thing that turns the lights on in your life and propels you to make real change, once and for all," Mallory says. "I want you to wake up and stay awake." For anyone hungry for a richer life, or tired of coasting through life in a "cruise control" mindset, Living Fully is the ultimate invitation to embrace abundance and joy-and not look back!"--